Voices Of Islam In Southeast Asia - FEALY, Greg (Iseas, 2007)
The Msulim communities of Southeast Asia are diverse, complex and increasingly influential in the broader Islamic world. However , the extraordinary breadth of practices and views across the Muslim world is not widely understood outside the region, often because of the difficulty of locating and putting in context the material produced by Muslims themselves.